TEACHER EMPOWERMENT:A COMPARATIVE STUDY OF URBANPRIVATE & GOVERNMENT SECONDARY SCHOOL TEACHERS OF AGRA DISTRICT - Varma, Kavita (International Journal of Psychosocial Rehabilitation, 2020)
Teachers are the sources of true knowledge and information. They provide education and shaped future of their students. And this will happen when teacher will be empowered. Empowerment is necessary for successful teacher. An empowered teacher can mould and change the mind and life of students. The present research designed to study and compare the teacher empowerment of urban private and government secondary school teachers. Descriptive survey method was used. Secondary schools were selected through convince sampling method and secondary school teachers were selected through simple random method. AmitKauts and HarveenKaur’s Teacher Empowerment Scale was used to collect data. Mean, S.D. and t- test were used to draw the conclusions. Finding of the study shows that no significant difference is found between teacher empowerment of urban private and government secondary school teachers.